2018
DOI: 10.1002/dmrr.3088
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral atherosclerotic profile in patients with type 1 diabetes warrants a thorough vascular assessment of asymptomatic patients

Abstract: Aims Epidemiological data on subclinical atherosclerotic disease in type 1 diabetes mellitus (DM1) are scarce. We aimed to estimate the subclinical atherosclerosis profile of asymptomatic patients with DM1 and an abnormal ankle‐brachial index (ABI). Material and methods In a cross‐sectional design (http://ClinicalTrials.gov Identifier: NCT02910271), we estimated ABI in 289 consecutive asymptomatic patients with DM1. An abnormal ABI led to measurements of toe‐brachial index (TBI) and peripheral doppler ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Exclusion criteria were: i) symptomatic intermittent claudication according to Edinburgh Claudication Questionnaire [8]; ii) previous diagnosis of peripheral artery disease, diabetic foot or leg amputation; iii) previous diagnosis of cerebrovascular disease iv) end-stage renal disease; and v) ongoing pregnancy. A detailed description of this trial has been reported elsewhere [7]. The study protocol conformed to the ethical guidelines of the Declaration of Helsinki, and was approved by Ramón y Cajal ethics committee (Date of approval: January 22, 2016; Reference number: 464/15).…”
Section: Study Populationmentioning
confidence: 99%
“…Exclusion criteria were: i) symptomatic intermittent claudication according to Edinburgh Claudication Questionnaire [8]; ii) previous diagnosis of peripheral artery disease, diabetic foot or leg amputation; iii) previous diagnosis of cerebrovascular disease iv) end-stage renal disease; and v) ongoing pregnancy. A detailed description of this trial has been reported elsewhere [7]. The study protocol conformed to the ethical guidelines of the Declaration of Helsinki, and was approved by Ramón y Cajal ethics committee (Date of approval: January 22, 2016; Reference number: 464/15).…”
Section: Study Populationmentioning
confidence: 99%
“…We conducted an observational cross-sectional study including 60 asymptomatic T1DM-patients, from a larger cohort (clinicaltrials.gov Identi er: NCT02910271) designed to comprehensively address their subclinical atherosclerosis pro le [7]. T1DM required age at onset of diabetes <30 yr-old, previous episode of ketoacidosis or diabetic autoimmunity, and mandatory use of insulin for survival, as de ned by ADA criteria.…”
Section: Study Populationmentioning
confidence: 99%
“…Exclusion criteria were: i) symptomatic intermittent claudication according to Edinburgh Claudication Questionnaire [8]; ii) previous diagnosis of peripheral artery disease, diabetic foot or leg amputation; iii) previous diagnosis of cerebrovascular disease iv) end-stage renal disease; and v) ongoing pregnancy. A detailed description of this trial has been reported elsewhere [7]. The study protocol conformed to the ethical guidelines of the Declaration of Helsinki, and was approved by Ramón y Cajal ethics committee (Date of approval: January 22, 2016; Reference number: 464/15).…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations